POROPERM CONTROLS IN OUTCROP ANALOGS FOR “ORDOVICIAN” FRACTURED CARBONATE RESERVOIRS IN THE SUPHANBURI BASIN,WESTERN THAILAND - Bunpitaksakul, Teerasak (Bulletin of Earth Sciences of Thailand, 2021)
Ordovician carbonate outcrops in Suphanburi Province, region of western Thailand are composed of highly metamorphosed carbonates. Previously these rocks were mapped as Ordovician limestones. The lithologies are actually composed of a variety of “Mylonitic marbles,” based on the classification of protolith, texture and mineral composition. The dominant fracture orientation is NW-SE in the studied outcrops. Stable isotopic study focused on calcite-filled fractures (with different orientations) along with calcite-vein cements in various metamorphosed hosts in variably deformed and thrusted Ordovician carbonates of the Thung Song Group. Samples were collected in quarry faces across three areas. Stable isotope crossplots of carbon and oxygen (C-O), using texture-aware isotope samples, define variable, but related, fluid-cement histories. The covariant C-O stable isotope plotfields indicate two trends. The first is a very hot fluid system tied to late mesogenetic/metamorphic alteration driving thermal reequilibration in calcite cement matrix and in calcite filled fractures with NW-SE and NE-SE trends. These are likely orogenic responses driven by the Indosinian (Triassic) orogeny.nThe second trend or plotfield indicates a diagenetic overprint seen in the latest calcite cements from speleothems and calcite filled N-S trending fractures. These samples occur in an uplifted telogenetic setting, driven by Cenozoic tectonics and isostatic uplift. The two distinct C-O signatures suggests a secondary porosity potential, which can be useful as an analogy in subsurface investigations via the integration of values from equivalent drill cuttings, fracture orientation measurements from open hole logs, and identification of unconformities in seismic images. Such integration will better define likely zones of porosity development in possible “uplift plays” in this carbonate unit in the subsurface in the nearby Suphanburi Basin.